Impulse ventilation in underground car parks: The influence of parked cars in smoke control - Viegas, J. (2010)
Impulse ventilation systems (IVS) are used to provide ventilation for underground car parks and to control the smoke in the event of fire. In this paper, the influence of the parked cars in the smoke control is studied using CFD simulations. A sensitivity analysis, considering important parameters as the number of parked cars and the height of the car park, is carried out. The results from a simplified analytical model for the flow field near the ceiling are compared with CFD simulations. It is shown that the obstruction caused by parked cars reduces the smoke control flow rate and the average velocity of the flow; therefore, it reduces the efficacy of the smoke control. It is also shown that the simplified model is able to reproduce approximately the boundary of the smoke. This simplified model is intended to support a first approach of the design of IVS.